Prognostic role of RECK in pathological outcome‐dependent buccal mucosa squamous cell carcinoma. (15th November 2019) - Chen, Hung‐Chih; Tseng, Yu‐Kai; Shu, Chih‐Wen; Fu, Ting‐Ying; Liou, Huei‐Han; Huang, Cheng‐Hui; Chen, Chien‐Chou; Wang, Jyh‐Seng; Wu, Pi‐Chuang; Ger, Luo‐Ping; Hung, Wen‐Chun; Liu, Pei‐Feng
Abstract: Background: Buccal mucosal squamous cell carcinoma (BMSCC) is an aggressive oral cancer. Moreover, reversion‐inducing cysteine‐rich protein with Kazal motifs (RECK) is a well‐known tumor suppressor in many cancers. Our aim was to investigate the association of RECK expression with prognosis in BMSCC patients with different clinicopathological features. Materials and Methods: The expression level of RECK was determined by immunohistochemistry using tissue microarrays containing specimens from 193 BMSCC patients. The association of RECK expression with outcomes in BMSCC patients stratified by different clinicopathological features was analyzed by Cox proportional hazards models. Results: The low expression level of RECK was associated with shorter disease‐specific survival, especially in patients with age >40 years, moderate or poor cell differentiation, advanced pathological stage, and history of postoperative radiotherapy. However, the low expression level of RECK was not associated with poor disease‐free survival, except in BMSCC patients with age ≦40 years, advanced pathological stage and lymph node metastasis. Furthermore, RECK‐knockdowned cells showed higher cell viability and abilities of invasion/migration, indicating that RECK might be a tumor suppressor for tumor progression in oral cancer. Conclusion: The low expression of RECK might be a potential prognostic biomarker for pathological outcome‐dependent BMSCC patients.